“Somos ensinados a pensar em sexo”: representações sociais de masculinidades e de amor em travestis homens gays e homens heterossexuais - Bussinger, Rebeca Valadão (2013)
Accomplished researches in male’s zone showed that certain groups’ accession and identification to some set of rules and behaviors, that define the human being, implies illness and submission to a regime that supposedly offer them advantages and power. Understand how different groups constitute themselves, concerning the sexual social division, become relevant, especially if we consider subjects that don’t obey the pattern that defines men and women’s behavior. This thesis looked for investigate love between individuals with different gender identity and sexual orientation, and male’s social representation, specifically: identify and analyze love between travestis, gay men and heterosexual men; capture prejudice and discrimination experiences lived due to gender identity and sexual orientation. The research was accomplished in two steps: semi structured interviews with 21 travestis; questionnaires, with open and closed questions, to 52 gay men, 40 heterosexual men and to 39 travestis. The collected data, on the first, round were submitted to the categorical thematic content analysis procedure. The collected data of the second round were made on the ALCESTE software. Heterosexual men represent masculinity from a evolutionary perspective, based on the biological and scientific point of view, that discards culture influences on the identity and sexual gender constitution. On the gay men we found approaches of the subjects representations to the hegemonic masculinity, tightly identified to the heterosexual men’s image, as well as the elements that now bring out approaches, sometimes detachment of that pattern. The travestis also utilize elements of the hegemonic masculinity’s idea to construct that representation, basing it on the construction of strong and manly men’s model, whereupon don’t identified themselves, but direct their desire. The three groups represent love as an element that is strange to masculinity, since that this is the object that belongs to the femininity. Love distances itself from the construction of heterosexual men’s social representation; it’s an weird and rowdy element to the gay men’s representation and value which corresponds to an ethics to the travestis’s group. In this sense, the prejudice and discriminations experiences almost don’t change the preparation of heterosexual’s representation; strongly influence the construction of men and women’s image, wherein gay men and travestis foster their identification. We conclude betting on the defense of practices and gender-diverse identities emergency as a potent device to the destabilization of male’s domination pattern to sex and identity determination.